Análise do potencial biotecnológico do sisal: uma revisão - Generoso, Gabriel Brito (Universidade Federal de São Carlos, 2021)
Sisal (Agave sisalana) is a plant originated from Central America, cultivated in a major part of brazilian semiarid, especially in Bahia region. Its main utilization consists in the defibrament of its leaves for use in the textile industry, in the production of strings, carpets and mats. Only 4% of the plant is utilized in the defibrament, generating a great amount of waste that is discarded in the environment. That waste, however, has very important industrial applications that goes far beyond the textile industry. The sisal waste is a producer of biosurfactants, among it more than twenty exclusive saponins, that are used in several diverse industries. The sisal waste is capable of eliminating disease-vectors mosquito larvae, agriculture plagues nematodes larvae that attacks important agricultural crops and has action against goat, sheep and chicken parasites. It is also a feedstock for biogases bioreactors and an important producer of celullosic ethanol, has a great antimicrobial activity against pathogens microorganisms, it’s a source of inulin and d-Mannitol, two important sugars in the production of diet food, among other uses. The biotechnological potential analysis of this waste proves that there is no reason for that waste to be discarded in the environment, when it can be used industrially. This paper encourages industries to look for more ecological and less expensive alternatives in its productions, economically encouraging the sisal production in brazilian territories, devastated by poverty and human subsistence, as well as stimulating the search for new uses to these products.
Sisal biotechnological potential analysis: a review
Keywords: Sisal; Biotecnologia; Indústria; Biotechnology; Industry; CIENCIAS AGRARIAS::AGRONOMIA; CIENCIAS BIOLOGICAS::BIOLOGIA GERAL; CIENCIAS BIOLOGICAS::BOTANICA